How can management ability promote green technology innovation of manufacturing enterprises? Evidence from China - Guang-lin, Xu; Tao, Meng (Frontiers in Environmental Science, 2023)
Abstract: In the context of the digital economy, digital transformation is an important way for traditional manufacturing enterprises' management to improve their green technological innovation, and internal control also plays an important role in ensuring this. The research sample for this paper is A-share manufacturing listed companies from 2008 to 2019. According to the findings, the stronger the management ability, the higher the performance of green technological innovation. Internal control quality has a significant regulatory effect on management's ability to improve green technological innovation performance; digital transformation plays a partial intermediary role in the influence of management ability on green technological innovation. We also discover that managerial competence is positively related to green technological innovation performance in both state-owned and non-state-owned enterprises, and that internal control has a significant positive regulating effect on the relationship between them. However, the role of digital transformation as an intermediary is not obvious in non-state-owned enterprises. Based on this, some recommendations are made, such as emphasizing management skill development, deepening digital transformation, improving internal control, and increasing government support.